A Case of Severe Tricuspid Stenosis of Rheumatic Origin - Rahman, MT; Das, M; Ullah, M; Rahman, Z; Hossain, A; Sayami, LA; Roy, SS; Majumder, AAS (Cardiovascular Journal, 2011)
Tricuspid valve stenosis is a valvular heart disease which results in the narrowing of the orifice of the tricuspid valve of the heart. It’s relatively a rare condition. It is almost always caused by rheumatic fever and is generally accompanied by mitral stenosis.Other rare causes include carcinoid syndrome, endocarditis, endomyocardial fibrosis, lupus erythematosus, right atrial myxoma and congenital tricuspid atresia. Here we describe a patient with history of prior CMC presented with severe Tricuspid Stenosis with Tricuspid Regurgitation (Grade-IV), Mitral Restenosis (Severe), Mitral Regurgitation (grade-1+), Aortic Stenosis (Mild) and Aortic Regurgitation (Grade-2). Keywords: Tricuspid stenosis; Rheumatic heart disease; Valvular heart disease. DOI: http://dx.doi.org/10.3329/cardio.v3i2.9197 Cardiovasc. J. 2011; 3(2): 235-238